Rehabilitation Technical Standard of "WU YIN TIAO SHEN （Five-Element Music Regulates Emotions）" - LI Li; ZHOU Xia; WANG Qin; MA Yuxia; SONG Jingjie; QIN Zhaomei (康复学报)
The music of five-element music is a form of traditional Chinese music with different tones (Jue, Zhi, Gong, Shang, Yu ) corresponding to the ancient five elements (Wood, Fire, Earth, Gold and Water). Since the advent of "Huangdi Neijing (Inner Canon of Huangdi)", the five-element music has been an important method for treating diseases, especially emotional disorders. Based on the five-element music in traditional Chinese medicine, the rehabilitation therapy of "WU YIN TIAO SHEN" combines the Kai Tianmen technique [acupoint massage on Zanzhu (BL 2)] and scalp acupuncture treatment, which is helpful to relieve the mind and body, and relieve anxiety and depression. The establishment of the rehabilitation technical standard of "WU YIN TIAO SHEN" aims to standardize the management and guide the practitioners of traditional Chinese medicine, rehabilitation therapists, psychotherapists, and music therapists to correctly use the rehabilitation technology of "WU YIN TIAO SHEN" for rehabilitation treatment. This standard includes the technical scope, normative reference documents, terms and definitions [targeted population, practitioner, flat pricking method, oblique pricking method, five-element music, scalp acupuncture, Kai Tianmen technique, WU YIN TIAO SHEN method, emotional music therapy, mutual generation among the five elements, mutual controlling of the five elements, fainting during acupuncture, the disorder of seven emotions], indications and contraindications, efficacy evaluation (mental health evaluation, quality of life assessment), five-element music tone selection, implementation steps and requirements [preparation (environmental requirements, instruments preparation, position and posture preparation, practitioner preparation), implementation process (the five elements music playing, Kai Tianmen technique, TIAO SHEN needling method), treatment time and frequency, precautions], and other aspects. This operational standard could be applied to guide the professionals (such as practitioners of traditional Chinese medicine, rehabilitation therapist, psychotherapists and music therapists, etc.) to carry out "WU YIN TIAO SHEN" therapy, with clinical applicability, safety and effectiveness.